Mangrove Cover and Shoreline Changes Detection using Multi-Temporal Landsat Imagery and Digital Shoreline Analysis System (DSAS) in Labuhanbatu Regency, Indonesia - Samsuri; Anita Zaitunah; Nailatul Amaliah; Yohanes Budi Sulistioadi; Duryat (Jurnal Sylva Lestari, 2026)
Understanding the dynamics of the relationship between shoreline change and mangrove forest cover change is important for a foundation in mangrove and coastal forest management. The study aimed to analyze multitemporal changes in mangrove cover and shoreline in coastal areas and to investigate the correlation between these changes from 2011 to 2024. The research used remote sensing data to derive mangrove cover changes and detect shoreline changes from Landsat images acquired in 2011, 2015, 2019, and 2024. Land cover changes were examined using the operational land imager sensor, bands 3 and 6 of Landsat 8 images and bands 2 and 5 of Landsat 5 images, and shoreline changes were measured using the digital shoreline analyses system (DSAS). The result showed a reduction of 580.07 ha (26.48%) in mangrove cover area over eight years (2011-2019), followed by an increase of about 1,931.59 ha (54.54%) in 2024. Low abrasion (0.01-108.41 m) and low accretion (0-106.78 m) per four-year interval dominate in shoreline change. However, the Pearson correlation showed a moderate but non-significant association between changes in mangrove cover and shoreline changes (r = 0.307, p = 0.266). These results demonstrate that the correlation between mangrove cover change and shoreline change is non-linear, suggesting that shoreline change is affected not only by mangrove change but also by various other factors, including sedimentation events. It indicates that additional factors, including geomorphological dynamics, significantly influence mangrove forest dynamics. Keywords: abrasion, change detection, land cover, mangrove, shoreline